High resolution SIMS analysis of arsenic in rice - Moore, K; Grovenor, C; Hawes, C; McGrath, S; Zhao, F (2013)
Determining the distribution of trace elements in biological materials with subcellular resolution is very challenging but vitally important in order to understand their mechanisms of uptake. Rice grain is efficient in the accumulation of arsenic (As) in the grain, potentially posing a severe health risk to millions of people in South-East Asia. The NanoSIMS is a state-of-the-art microscope capable of high resolution chemical imaging (down to 50 nm) and detecting very low elemental concentrations (parts-per-million levels). This makes it ideally suited for trace element localisation in biological materials. This paper shows how the NanoSIMS can be used to investigate the localisation of As in rice grain at high resolution and how different treatments result in different distributions in the grain. The precise location of parts-per-million As concentrations and its localisation with other elements at the subcellular scale in rice roots are also shown. Copyright © 2012 John Wiley and Sons, Ltd. Copyright © 2012 John Wiley and Sons, Ltd.